Mapping the path of a gendered CSR: toward a specific framework for family SMEs - Costanza, Francesca; Minà, Anna; Paternostro, Sergio (Piccola Impresa / Small Business, 2022)
Extant literature on gender equality issues and corporate social responsibility (CSR) is copious but fragmented. Additionally, it is mainly focused on large firms and public companies. There is, therefore, an opportunity to assess the ‘state of the art’ of existing inquiry. Through a content analysis of 104 papers, we identify key themes, methodological approaches, and phases of research development. These efforts converge on a conceptual framework bringing together the landscape of current knowledge, which we then adapt to shed light on gendered CSR in family SMEs, and to formulate a research agenda. With this research approach, we fit in the debate on gender diversity in family SMEs’, shedding light on the role of women in contributing to financial and non-financial performance; thereby we wish to provide a contribution to the call for papers “Piccola Impresa/Small Business - Women in Small and Medium Family Firms: Theory and Practice”.